The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11356-020-10591-9
|View full text |Cite
|
Sign up to set email alerts
|

Oil sludge washing with surfactants and co-solvents: oil recovery from different types of oil sludges

Abstract: Different physicochemical and biological treatments have been used to treat oil sludges, and oil recovery techniques are preferred such as oil sludge washing (OSW) with surfactants and co-solvents. Toluene is commonly used as co-solvent, but it is non-benign to the environment. This study tested alternative co-solvents (n-pentane, n-hexane, cyclohexane, and isooctane) at 1:1 and 2:1 C/OS (co-solvent to oil sludge ratio). Also, this study evaluated the effect on the oil recovery rate (ORR) of three main paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…There are two moieties of the rhamnolipids, one or two l -rhamnose hydrophilic molecules with a glycosidic linkage to the hydrophobic groups comprising one or multiple β-hydroxylated fatty acids. The diversity in chemical structures of RLs , features their wide-ranging functionalities. , In the past two decades, experimental studies have shown promising results of using RLs for environmental remediation. By improving the production method, the production cost of RL has become more suitable for massive usage. , Nevertheless, the naturally produced RLs usually contain several RLs homologues and congeners. Understanding the micellar properties and the interfacial behavior of RLs in their pure states or in mixtures, as well as their interactions with hydrocarbons, is the key to advance future development.…”
Section: Introductionmentioning
confidence: 99%
“…There are two moieties of the rhamnolipids, one or two l -rhamnose hydrophilic molecules with a glycosidic linkage to the hydrophobic groups comprising one or multiple β-hydroxylated fatty acids. The diversity in chemical structures of RLs , features their wide-ranging functionalities. , In the past two decades, experimental studies have shown promising results of using RLs for environmental remediation. By improving the production method, the production cost of RL has become more suitable for massive usage. , Nevertheless, the naturally produced RLs usually contain several RLs homologues and congeners. Understanding the micellar properties and the interfacial behavior of RLs in their pure states or in mixtures, as well as their interactions with hydrocarbons, is the key to advance future development.…”
Section: Introductionmentioning
confidence: 99%
“…The co-solvent used was cyclohexane (high-purity, HPLC grade, Fisher Scientific). Cyclohexane was selected in a previous oil recovery study from OSW processes (Ramirez et al 2020). It was found that the oil recovery rates were not significantly different between cyclohexane and one of the most commonly used solvents, toluene.…”
Section: Surfactants and Co-solventmentioning
confidence: 99%
“…The residuals were obtained at bench scale from the following OSW process. Briefly, the oil sludge (5 g), surfactant [5:1 ratio to oil sludge and at 5CMC, critical micelle concentration; the highest ratio and concentration used in previous oil recovery studies with these oil sludges samples (Ramirez and Collins 2018;Ramirez et al 2020)], and cyclohexane (1:1 ratio to oil sludge) were added to a 40-ml vial. The vial was then agitated at 250 rpm for 60 min and left for 12 h to settle.…”
Section: Oil Sludge Washingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their study, RL has the oil recovery rate among the highest, which is around 40–70%. They have also found that the concentration of the surfactant used has a minimal effect on the oil recovery performance . However, the application ratio of surfactant-to-oil (S/O) does have a great impact on the surfactant’s performance in the presence of hydrocarbon as a cosolvent.…”
Section: Introductionmentioning
confidence: 99%